2023
DOI: 10.3201/eid2906.221685
|View full text |Cite
|
Sign up to set email alerts
|

Association of Persistent Symptoms after Lyme Neuroborreliosis and Increased Levels of Interferon-α in Blood

Abstract: Patients who have Lyme neuroborreliosis (LNB) might experience lingering symptoms that persist despite antibiotic drug therapy. We tested whether those symptoms are caused by maladaptive immune responses by measuring 20 immune mediators in serum and cerebrospinal fluid (CSF) in 79 LNB patients followed for 1 year. At study entry, most mediators were highly concentrated in CSF, the site of the infection. Those responses resolved with antibiotic therapy, and associations between CSF cytokines and signs and sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies have shown multiple elevated immune markers in both acute Lyme disease (IL-6, IL-8, IL-12, IL-18, IFN-γ, CXCL12, CXCL13) and PTLDS (IL-6, IL-23, IFN-α, CCL19) [ 46 , 47 , 48 , 49 ]. A recent study indicated that in patients with acute neuroborreliosis whose symptoms persisted despite antibiotic therapy, serum IFN-α remained elevated from the initial testing at the onset of acute neurologic infection to each of the subsequent post-antibiotic treatment timepoints, with the highest levels corresponding to severe disease [ 50 ]. This finding, complemented by the observation that IFN-α levels were elevated in the CSF but then returned to normal after antibiotic therapy, supports the possibility that initial infection with Borrelia burgdorferi serves as a trigger for persistent symptoms due to an interferonopathy.…”
Section: Proposed Mechanisms Of Symptom Persistencementioning
confidence: 99%
“…Studies have shown multiple elevated immune markers in both acute Lyme disease (IL-6, IL-8, IL-12, IL-18, IFN-γ, CXCL12, CXCL13) and PTLDS (IL-6, IL-23, IFN-α, CCL19) [ 46 , 47 , 48 , 49 ]. A recent study indicated that in patients with acute neuroborreliosis whose symptoms persisted despite antibiotic therapy, serum IFN-α remained elevated from the initial testing at the onset of acute neurologic infection to each of the subsequent post-antibiotic treatment timepoints, with the highest levels corresponding to severe disease [ 50 ]. This finding, complemented by the observation that IFN-α levels were elevated in the CSF but then returned to normal after antibiotic therapy, supports the possibility that initial infection with Borrelia burgdorferi serves as a trigger for persistent symptoms due to an interferonopathy.…”
Section: Proposed Mechanisms Of Symptom Persistencementioning
confidence: 99%
“…T-cell reactivity and antibody development after acute LD are of particular interest in the setting of post-treatment Lyme disease (PTLD), an infection-associated chronic illness of poorly understood etiology, and there is growing evidence that upregulation of interferons after early stages of LD may be associated with PTLD pathogenesis. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: We were intrigued by Hernandez et al’s recent important study linking persistent subjective symptoms after Lyme neuroborreliosis in Europe with increased interferon (IFN) α levels in blood ( 1 ). Their findings align with our earlier study in the United States, which showed an association between persistent objective neurocognitive deficits, despite antibiotic treatment for Lyme disease, and elevated blood IFN-α activity ( 2 ).…”
mentioning
confidence: 99%
“…A noteworthy difference between the 2 studies is the method of IFN-α detection. Hernandez et al ( 1 ) relied on a bead-based immunoassay to directly measure IFN-α levels, whereas we used a functional cell-based assay and quantitative real-time PCR to assess IFN-α activity ( 2 , 3 ). Direct quantitation of IFN-α can be challenging, as highlighted by the fact that concentrations for some study participants in the Hernandez et al article appeared to fall below the limit of quantitation, thus complicating the analysis and interpretation of the data.…”
mentioning
confidence: 99%